Size of the Optic Nerve Head and Its Relationship with the Thickness of the Macular Ganglion Cell Complex and Peripapillary Retinal Nerve Fiber Layer in Patients with Primary Open Angle Glaucoma - Nobuko Enomoto; Ayako Anraku; Kyoko Ishida; Asuka Takeyama; Fumihiko Yagi; Goji Tomita (Journal of Ophthalmology)
Purpose. To evaluate the relationships among the optic nerve head (ONH) area, macular ganglion cell complex (mGCC) thickness, circumpapillary retinal nerve fiber layer (cpRNFL) thickness, and visual field defects in patients with primary open angle glaucoma (POAG). Methods. This retrospective study included 90 eyes of 90 patients with POAG. The ONH area, rim area, mGCC thickness, and cpRNFL thickness were measured using optical coherence tomography. Mean deviation (MD) was measured using standard automated perimetry. The relationships among clinical factors including age, refraction, the ONH area, the rim area, the mGCC thickness, the cpRNFL thickness, and MD were evaluated using correlation coefficients and multiple regression analyses. Results. The significant correlation of the ONH area with refraction (r=0.362, P<0.001), the mGCC thickness (r=0.225, P=0.033), and the cpRNFL thickness (r=0.253, P=0.016) was found. Multiple regression analysis showed that the ONH area, rim area, and MD were selected as significant contributing factors to explain the mGCC thickness and cpRNFL thickness. No factor was selected to explain MD. Conclusions. The ONH area, in other words, the disc size itself may affect the mGCC thickness and cpRNFL thickness in POAG patients.